Independent mobility and physical activity among children residing in an ultra-dense metropolis - Huang Wendy Y.; Feng Jie; Wong Stephen H. (Translational Exercise Biomedicine)
Independent mobility (IM), which is defined as the freedom of children moving without adult supervision, has been found to be positively associated with physical activity (PA). This study explored IM by sociodemographic factors and type of neighborhoods and its association with PA among children in Hong Kong.